PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KINERJA KARYAWAN DI PANGAREN BEACH HOTEL PADANG - Selfitri, Yuli (journal of residu, 2019)
The problem in this research is not maximal performance results performed by the employee in Pangaren Beach Hotel Padang. This study aimed to determine the effect of knowledge management on employee performance Pangaren Beach Hotel in Padang. This type of research is quantitative, using correlational design, with a causal associative approach. The population in this research were 116 employees in Pangaren Beach Hotel Padang. The sampling technique using proportionate stratified random sampling. Thus the number of samples in this study was 90 people. Data were collected using primary and secondary data. For knowledge management is taken by using konsioner closed while performance data is secondary data. Data were analyzed with linear regression hused SPSS version 16. Based on the results of data analysis: (1) Knowledge management karyanwan in Pangaren Beach Hotel Padang, namely 74.77% are in the good category, (2) Karyanwan employee performance in Pangaren Beach Hotel Padang, namely 72.22% are in the good category, (3) Knowledge management  have a significant effect on the performance of employees in Pangaren Beach Hotel Padang, by 17.7%, and 82.3% influenced by other variables that are not discussed in this study.